Clinicopathological, radiological and bronchoscopic evaluation of suspected lung malignancy - Mathew, Stacey Boban; S. Chandra, Sharath K.; Mynalli, Adarsh B.; Kandal, Irfan (International Journal of Research in Medical Sciences, 2022)
Background: This study was conducted to evaluate the clinical, pathological and radiological profile of suspected lung malignancy and its correlation with bronchoscopic findings. Methods: A hospital based prospective study was conducted in the department of pulmonary medicine on 74 patients who were suspected with lung malignancy, clinically or radiologically. Following a detailed clinical examination, chest x-ray and CECT thorax, patients were included in the study and were subjected to bronchoscopy. Based on the bronchoscopic findings BAL, TBNA, forceps biopsy and TBLB were performed. Results: Out of 74 patients, most of them belonged to the age group of 51-65 years. Majority were males. Cough was the most common symptom. 51 patients had weight loss and 48 had associated reduced appetite. 50 (67.6%) were smokers. Out of them 43 (86%) were beedi smokers. In CT thorax, most common presentation was mass lesion followed by consolidation, nodules and interstial thickening. Right side was the most common side involved. Bronchoscopy revealed intraluminal growth as the most common finding and the most common pattern noted was fungating growth. Squamous cell carcinoma was the most common cell type noted in 9 (27.03%) followed by adenocarcinoma and small cell carcinoma. Squamous cell carcinoma presented more commonly as central mass with intraluminal growth and adenocarcinoma presented more commonly as peripheral lesions with extraluminal compression in bronchoscopy. Conclusions: Elderly smokers with cough and loss of appetite with weight loss can be suspicious of lung malignancy. CT and bronchoscopy are essential for the diagnosis of lung malignancy.